Buddhism and Its History in Central Asia - ZUURIDINOV, Oskonbai (Scientific Journal of Faculty of Theology, 2020)
This article mentioned that general history of Buddhism and notes the place of Hinduism in its comprehension. We have considered appeared of ancient Indian Buddhism to spread on Central Asia. And as stated in the epic Manas to gave a scientific assessment of the remnants of Buddhism in Kyrgystan.